2017
DOI: 10.1111/jgh.13758
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver stiffness measurements and fibrosis scores following sofosbuvir based treatment regimens without interferon

Abstract: Sofosbuvir-based treatment resulted in a clinically significant improvement in parameters of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
51
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 46 publications
15
51
0
1
Order By: Relevance
“…Furthermore, the present study is important as it also demonstrated that LS continued to decrease significantly from baseline to 72 weeks after EOT in the non‐SVR group, excluding at 48 weeks. Previous studies reported that LS decreased in SVR patients during a short period of time, but to our knowledge there are no reports demonstrating that oral dual therapy with DCV and ASV can improve the histopathological features over the 2‐year term regardless of the treatment efficacy. LS is influenced not only by the degree of liver fibrosis, but also by inflammatory activity .…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the present study is important as it also demonstrated that LS continued to decrease significantly from baseline to 72 weeks after EOT in the non‐SVR group, excluding at 48 weeks. Previous studies reported that LS decreased in SVR patients during a short period of time, but to our knowledge there are no reports demonstrating that oral dual therapy with DCV and ASV can improve the histopathological features over the 2‐year term regardless of the treatment efficacy. LS is influenced not only by the degree of liver fibrosis, but also by inflammatory activity .…”
Section: Discussionmentioning
confidence: 98%
“…In univariant and multivariate analysis, failure to improve TE measurements following treatment was associated with relapse and with low baseline LS values [9].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, after treatment, the regression of liver fibrosis was assessed in both groups with the use of fibrosis markers such as PLT, FIB-4, and APRI, that have been demonstrated to be accurate predictors of hepatic fibrosis in HCV patients [34][35][36] . Several studies have demonstrated a significant decline in liver fibrosis, as determined by FIB-4 and APRI scores in treatment with Sofosbuvir-based regimens [45,46] . In the present study also, a significant reduction in FIB-4 and APRI scores was observed in the Sofosbuvir plus RBV group; moreover, in evaluating the stages of fibrosis, the PLT count was higher at EOT than the baseline.…”
Section: Discussionmentioning
confidence: 99%